Observing Nightlights from Space with TEMPO - James Carr; Xiong Liu; Brian Baker; Kelly Chance (International Journal of Sustainable Lighting, 2017)
The Tropospheric Emissions: Monitoring of Pollution (TEMPO) instrument is a NASA Earth Venture Instrument set to fly in the 2018-2021 timeframe and cover North America from a geostationary orbit. TEMPO is a powerful spectrometer sampling UV and visible wavelengths in two channels (290-490 nm and 540-740 nm) in 0.2 nm steps. This spectroscopic capability will enable TEMPO to characterize many types of artificial lighting at night in addition to its regular daytime air quality and atmospheric chemistry mission. This paper describes the TEMPO instrument and our planned approach to make nighttime observations. A spectral retrieval algorithm will estimate the contributions from sources in a spectral library to map out the usage of various types of lighting (e.g., Hg vapor, high and low pressure Na vapor, LED, fluorescent, and incandescent) over North America. We calculate the sensitivities of such nightlight retrievals using the measured properties of our flight detectors and optics, and conclude that TEMPO will complement well the VIIRS Day-Night Band for the study of artificial lighting at night from space by offering a new and powerful capability to discriminate between lighting types.